Analisa Kinerja Keuangan PT Astra Agro Lestari Tbk - Denny Erica (LPPM Universitas Bina Sarana Informatika, 2021)
PT Astra Agro Lestari Tbk is a company engaged in the management of plantation materials, such as palm oil, rubber, tea, chocolate and cooking oil. caters to various market segments, both at home and abroad with the code on the Indonesia Stock Exchange (AALI). PT Astra Agro Lestari can analyze the company's financial performance using the ratio analysis method on its financial statements on a regular basis, besides that it can be a benchmark for investors to invest in PT Astra Agro Lestari Tbk.